STRATEGI KOMUNIKASI GURU PONDOK DALAM MEWUJUDKAN AKHLAK SANTRI PONDOK PESANTREN IMAM DZAHABI - Desky Berampu (Bashirah, 2022)
Islamic boarding schools are places to study and have regulations that aim to make a santri able to have good morals in everyday life. The distance of children's lives from religious values is one of the real impacts of development and global access without a filter that can become strong enough to identity adhesive. The phenomenon of juvenile delinquency and other things that can damage the character of these students shows the importance of moral development carried out by the boarding school teacher to his students. The main goal of the Pondok teacher was trying to form a young generation who believes and fears Allah subhana wata'ala .able to devoted with parents and beneficial to others. This aroused the enthusiasm of the researchers to conduct observations at the Imam Dzahabi Islamic Boarding School, by looking at the communication strategies of the boarding school teachers to the students in fostering the student's morals at the boarding school. this study was a descriptive qualitative approach with observation, while the object of research is the teachers and students in this boarding school. The result shows the methods applied by the teacher in the strategy of fostering morals at the cottage, including; a) dialogue or discussion method, b) exemplary method, c) habituation method, d) advice method. In addition, there is a boarding guidebook that guides the students in living their lives while at the cottage, including; daily activities, weekly activities, boarding regulations, mosque regulations, and others.